Comparison of split skin thickness graft survival in diabetic and non-diabetic ulcer - Lamani, Yamanur P.; Reddy, M. Amarnath; Kalburgi, E. B.; Suhas, B. S. (International Surgery Journal, 2020)
Background: Split skin grafting is widely used surgical procedure for the treatment of ulcers. Graft survival depends on number of factors like vascularity, wound infection etc, diabetes is associated with endothelial dysfunction, neuropathy, wound infection which collectively affect the graft survival. Objective of this study was to compare the amount of graft uptake, the post-operative complications and survival of split thickness skin graft in diabetic and non-diabetic ulcer. Methods: In our prospective comparative study total 112 patients with ulcer were included of which 56 were diabetic and 56 were non-diabetic. All of them underwent split skin grafting as part of their wound management. Comparison was made between two groups in terms of amount of graft uptake, post-operative wound infection, revisional surgery, donor site infection. Results: Compared with non-diabetics, diabetics have significantly less graft uptake (p<0.001). out of 56 patients in diabetic group 4 (66.7%) underwent revisional surgery, out of 56 patients in non-diabetic group 2 (33.3) patients underwent revisional surgery (p value is <0.68) which is statistically insignificant. 3 (60%) out of 56 in diabetic group developed post-operative graft infection, 2 (40%) out of 56 in non-diabetic group developed graft infection (p=1, not significant). One patient in the study developed donor site infection. Among 112 cases, only 1 case had donor site infection with diabetic. Conclusions: Diabetes is associated with poor graft uptake and post-operative complication rates in patients undergoing split skin grafting.